
Example: Sue is 8 and twothird years older than Jill. The sum of their ages is 23 years. How old is Jill? Solution: Let 's' stand for Sue's age and 'j' stand for Jill's age. Sue is 8 and twothird years older than Jill: s = 8 + (2/3)j The sum of their ages is 23 years: s + j = 23 that means s = 23j s = 8 + (2/3)j substitute s = 23j 23j = 8 + (2/3)j 23  8 = j + (2/3)j 15 = (5/3)j 3 = (1/3)j 3 = j/3 j = 9 year old s = 23  j = 23  9 = 14 Jill is 9 years old and Sue is 14 years old. Example: Bob is three years older than Sally. The sum of the ages of Bob and Sally is seven. How old is Bob? Solution: Let 'b' stand for Bob's age and 's' stand for Sally's age. Bob is three years older than Sally: b = s + 3 The sum of the ages of Bob and Sally is seven: b + s = 7 s + 3 + s = 7 2s + 3 = 7 2s = 73 2s = 4 s = 2 b = s+3 = s +3 = 5 Bob is 5 years old. Example: Three times Sally's age five years ago is same as sixty less than six times her current age. How old is Sally? Solution: Let 's' be Sally's present age. Three years ago Sally's age is s  3 3(s5) = 6s  60 3s15 = 6s  60 6015 = 6s  3s 45 = 3s s = 45/3 s = 15 Directions: Solve the following word problems. 